Efficient and Tunable Electroluminescence from In Situ Synthesized Perovskite Quantum Dots. Issue 8 (28th January 2019) - Yu, Hongling; Wang, Heyong; Zhang, Jiangbin; Lu, Jun; Yuan, Zhongcheng; Xu, Weidong; Hultman, Lars; Bakulin, Artem A.; Friend, Richard H.; Wang, Jianpu; Liu, Xiao‐Ke; Gao, Feng
Abstract: Semiconductor quantum dots (QDs) are among the most promising next‐generation optoelectronic materials. QDs are generally obtained through either epitaxial or colloidal growth and carry the promise for solution‐processed high‐performance optoelectronic devices such as light‐emitting diodes (LEDs), solar cells, etc. Herein, a straightforward approach to synthesize perovskite QDs and demonstrate their applications in efficient LEDs is reported. The perovskite QDs with controllable crystal sizes and properties are in situ synthesized through one‐step spin‐coating from perovskite precursor solutions followed by thermal annealing. These perovskite QDs feature size‐dependent quantum confinement effect (with readily tunable emissions) and radiative monomolecular recombination. Despite the substantial structural inhomogeneity, the in situ generated perovskite QDs films emit narrow‐bandwidth emission and high color stability due to efficient energy transfer between nanostructures that sweeps away the unfavorable disorder effects. Based on these materials, efficient LEDs with external quantum efficiencies up to 11.0% are realized. This makes the technologically appealing in situ approach promising for further development of state‐of‐the‐art LED systems and other optoelectronic devices. Abstract : A straightforward route to produce in situ solution‐grown FAPbI3 perovskite quantum dots (PQDs) is demonstrated, which deliver optical and electrical properties comparable to the ex situ colloidal‐grown ones. These in situ grown PQDs also achieve high external quantum efficiencies (EQEs) up to 11.0% with tunable emissions ranging from 667 to 790 nm in LEDs based on pure‐halogen perovskite thin films.